Perlindungan Hukum Notaris dalam Penggunaan Klausula Eksonerasi dalam Akta Terkait Warkah yang Tidak Benar yang Diserahkan oleh Penghadap kepada Notaris - Dede Suriya Kusumah; Felicitas Sri Marniati; Dhody AR Widjadjaatmadja (CV Rewang Rencang, 2025)
In this study, the legal consequences of Notarial Deeds related to incorrect documents submitted by the appearers to the Notary and the Notary's legal protection in the use of exoneration clauses are discussed. From the research results, it can be obtained that the legal consequences of an authentic deed that is intentionally made with false information included, the Notarial Deed is null and void by court decision and the Deed becomes null and void by law its evidentiary force from the original authentic Deed to a Deed under hand and the inclusion of an exoneration clause as a form of legal protection for the Notary is not a guarantee of certainty for the Notary so that he will not be sued or sued in civil or criminal cases.